2014
DOI: 10.5946/ce.2014.47.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Endomicroscopy and Molecular Imaging in Barrett Esophagus and Stomach

Abstract: Detection of premalignant lesions in the upper gastrointestinal tract may facilitate endoscopic treatment and improve survival. Despite technological advances in white light endoscopy, its ability to detect premalignant lesions remains limited. Early detection could be improved by using advanced endoscopic imaging techniques, such as magnification endoscopy, narrow band imaging, i-scanning, flexible spectral imaging color enhancement, autofluorescence imaging, and confocal laser endomicroscopy (CLE), as these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…3, • " Video 1) detected more patients with intestinal metaplasia than did WLE (26/38 vs. 13/38, P = 0.011), in a prospective, randomized crossover trial that included 65 patients [92]. CLE consistently outperformed WLE in the detection of intestinal metaplasia and its diagnostic performance is similar to that of magnification-NBI [93]. However in a parallel group randomized controlled trial of CLE vs. WLE in 168 patients for the diagnosis of intestinal metaplasia, the difference in rates was not significant on a per-patient basis (45 % and 31 %, respectively, P = 0.074) [94].…”
Section: Stomachmentioning
confidence: 83%
“…3, • " Video 1) detected more patients with intestinal metaplasia than did WLE (26/38 vs. 13/38, P = 0.011), in a prospective, randomized crossover trial that included 65 patients [92]. CLE consistently outperformed WLE in the detection of intestinal metaplasia and its diagnostic performance is similar to that of magnification-NBI [93]. However in a parallel group randomized controlled trial of CLE vs. WLE in 168 patients for the diagnosis of intestinal metaplasia, the difference in rates was not significant on a per-patient basis (45 % and 31 %, respectively, P = 0.074) [94].…”
Section: Stomachmentioning
confidence: 83%
“…On the other hand, pCLE’s greatest disadvantage is its high cost, which can be a significant barrier to widespread clinical implementation. Other disadvantages can relate to availability, physician training in image interpretation, the extra time needed to view the images during endoscopy, and the role of the pathologist [ 58 , 59 , 60 ]. Using pCLE also could have a side effect in cases of allergy to the contrast agent, fluorescein, which is used to stain the tissues [ 61 , 62 ].…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Even though pCLE has been tested in several studies with promising results, it is not considered as a standard method for histopathological diagnosis, and its present role is rather ancillary. [5][6][7][8] Several studies have shown that pCLE may provide comparable or even better diagnostic accuracy compared with standard biopsies in patients with oesophageal adenocarcinoma (AC), [9][10][11] oesophageal squamous-cell cancer (SCC) 12,13 or gastric AC. 14,15 pCLE increases sensitivity and diagnostic accuracy for dysplasia or AC, if added up on high-definition endoscopy (with narrow-band imaging (NBI)) in patients with Barrett's oesophagus (BO).…”
Section: Introductionmentioning
confidence: 99%
“…pCLE can be used in the diagnostics through the entire gastrointestinal (GI) tract. Even though pCLE has been tested in several studies with promising results, it is not considered as a standard method for histopathological diagnosis, and its present role is rather ancillary 5–8 . Several studies have shown that pCLE may provide comparable or even better diagnostic accuracy compared with standard biopsies in patients with oesophageal adenocarcinoma (AC), 9–11 oesophageal squamous‐cell cancer (SCC) 12,13 or gastric AC 14,15 .…”
Section: Introductionmentioning
confidence: 99%